Prevalence of oral rehydration therapy use and associated factors among under-five children with diarrhea in Dangure, Benishangul Gumuz Region, Ethiopia/2018 - Haftom Gebrehiwot Misgna; Biratu Ebessa; Mekuria Kassa (BMC Research Notes, 2019)
Abstract Objectives This study aims to assess the prevalence of oral rehydration therapy use and associated factors among under-five children with diarrhoea in Dangure district, Benishangul Gumuz Region, Ethiopia/2018. Result A total of 615 under-five children who suffered from diarrhoea 2 weeks before the study were included and the response rate was 610 (99%). Among the total children participated in this study 189 (31%) were between 12 and 23 months with mean 23.5 and SD ± 6.9. Five hundred seventeen (84.8%) of mothers had access to oral rehydration therapy and 85% of mother’s home had taken less than 1 h distance from the health facility. The prevalence of oral rehydration therapy is 51%. Two hundred sixty-seven (43.8%) mothers mentioned correctly about the importance of oral rehydration therapy which is to replace fluid while other 243 (39.8%) mothers stated that oral rehydration therapy uses to decrease diarrhoea. Mother’s educational status, monthly income, knowledge of oral rehydration therapy, previous experience and seeking advice for treatment from health facilities were factors associated with oral rehydration therapy use.